VD_FINDINFO AI 188/10 - 141/2014 vom 16. Juni 2014 - VD Tribunal cantonal (2014)
RÉVISIONPRESTATION D'ASSURANCE, EXPERTISE PSYCHIATRIQUE, FORCE PROBANTE, RENTE D'INVALIDITÉ | 28 LAI, 17 LPGA, 8 LPGA, 88a RAI, 88bis RAI